Evaluation of efficacy and safety of Collashot C2 plus capsule in osteoarthritis patients - Deb, Bijoy; Gobaloussamy, Bhuvanesh; Murugesan, Sakthibalan; Sivakumar, Gayathri (International Journal of Research in Orthopaedics, 2024)
Background: Osteoarthritis (OA), the most prevalent joint disease, is marked by chronic joint pain and debilitating symptoms. Many drugs are available in the market for treating osteo arthritis symptoms but there is still need for drugs with least adverse effects. So, in this study, an attempt has been done with Collashot C2 plus capsule, a nutraceutical for treating OA symptoms. Methods: This is an outcome, quasi-experimental study where patients with OA were included. Patients were given capsule Collashot C2 plus daily for 3 months. A total of 30 male and female patients were included in the study. Changes from baseline to 12 weeks in knee pain intensity measured by pain visual analogue scale (VAS) and in Western Ontario and McMaster universities OA index (WOMAC) pain subscale, laboratory parameters, participant’s global assessment of improvement of OA were assessed. Adverse drug reactions were also observed during the study period. Results: There was a statistically significant improvement in the VAS pain scale, WOMAC pain score and in participant’s global assessment of improvement of OA at week 4, week 8, and week 12 compared to baseline (p<0.001) was observed. Conclusions: Collashot C2 plus capsule has proved to be very safe and effective in the management of OA Participants by reducing inflammation, providing adequate pain relief without causing any major side effects.